2022
DOI: 10.1002/smll.202204143
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Manipulation of Tetrahedral Units in Spinel Oxides for Boosting Water Oxidation

Abstract: the sluggish kinetics of oxygen evolution reaction (OER) for water splitting still hinders the wide application of this technology. Ru-and Ir-based oxides are highly active catalysts for OER, nevertheless, the scarcity and cost of Ru and Ir largely constrains the broad deployment of hydrogen production utilities. [4][5][6] To this end, transition metal oxide (TMO) electrocatalysts have been extensively investigated due to their earth-abundant and outstanding OER performance. [7][8][9][10] It is remarkable that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 78 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…158 While there has been considerable interest in the magnetic field-driven enhancement of the OER in spinel oxides in recent years, the majority of research has focused on spin dynamics. 159,160 Lyu 161 has presented the first strategy for manipulating the tetrahedral units in NiFe 2 O 4 (NFO) using magnetic fields to improve OER performance. Through their research, they found that the application of a magnetic field can cause Ni 2+ ions to migrate from the octahedral ( O h ) site to the tetrahedral ( T d ) site in mixed NFO spinels (Fig.…”
Section: Magnetic Field-enhanced Electrocatalysismentioning
confidence: 99%
“…158 While there has been considerable interest in the magnetic field-driven enhancement of the OER in spinel oxides in recent years, the majority of research has focused on spin dynamics. 159,160 Lyu 161 has presented the first strategy for manipulating the tetrahedral units in NiFe 2 O 4 (NFO) using magnetic fields to improve OER performance. Through their research, they found that the application of a magnetic field can cause Ni 2+ ions to migrate from the octahedral ( O h ) site to the tetrahedral ( T d ) site in mixed NFO spinels (Fig.…”
Section: Magnetic Field-enhanced Electrocatalysismentioning
confidence: 99%
“…Besides, Kan and co‐workers reported that a strong magnetic field can enable Ni 2+ to migrate from the octahedral (Oh) sites to the preferential tetrahedral (Td) sites in a mixed NiFe 2 O 4 (NFO) catalyst, showing better catalytic performance for OER. [ 87 ]…”
Section: Magnetic Field‐enhanced Electrocatalysismentioning
confidence: 99%
“…Xiao Lyu [30] found that the external magnetic field can force the Ni 2 + cation in mixed NiFe 2 O 4 (NFO) to transfer from the octahedral (Oh) site to the tetrahedral (Td) site. Under the alkaline condition, the current density of NFO affected by the applied magnetic field is twice higher than that of the original NFO.…”
Section: The Structure Regulation Induced By the Magnetic Fieldmentioning
confidence: 99%